2020
DOI: 10.1016/j.ijid.2019.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Indications and classes of outpatient antibiotic prescriptions in Japan: A descriptive study using the national database of electronic health insurance claims, 2012–2015

Abstract: To evaluate condition-specific antibiotic prescription rates and the appropriateness of antibiotic use in outpatient settings in Japan. Methods: Using Japan's national administrative claims database, all outpatient visits with infectious disease diagnoses were linked to reimbursed oral antibiotic prescriptions. Prescription rates stratified by age, sex, prefecture, and antibiotic category were determined for each infectious disease diagnosis. The proportions of any antibiotic prescription to all infectious dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 22 publications
(32 reference statements)
4
38
1
Order By: Relevance
“…The proportion of antimicrobial drugs that were unnecessary in the present study was higher than that in recent studies conducted outside Japan 8–10 but is similar to that in a recent Japanese study. 23 Even though the proportion of antimicrobial therapy for infectious diseases that generally do not require the use of antimicrobial drugs was lower in the present study than in recent studies, 8–10 23 the rate of unnecessary antimicrobial drugs in the present study still seems high. However, unlike other studies, 8–10 23 we investigated the evidence for physicians’ diagnoses of infectious diseases in addition to evaluating whether antimicrobial drugs were prescribed for infectious diseases that required antimicrobial therapy.…”
Section: Discussioncontrasting
confidence: 74%
“…The proportion of antimicrobial drugs that were unnecessary in the present study was higher than that in recent studies conducted outside Japan 8–10 but is similar to that in a recent Japanese study. 23 Even though the proportion of antimicrobial therapy for infectious diseases that generally do not require the use of antimicrobial drugs was lower in the present study than in recent studies, 8–10 23 the rate of unnecessary antimicrobial drugs in the present study still seems high. However, unlike other studies, 8–10 23 we investigated the evidence for physicians’ diagnoses of infectious diseases in addition to evaluating whether antimicrobial drugs were prescribed for infectious diseases that required antimicrobial therapy.…”
Section: Discussioncontrasting
confidence: 74%
“…We also included four other antibiotics, namely metronidazole, tinidazole, ornidazole, and furazolidone. 14 The appendix (pp [16][17] gives a full list of antibiotics in this study.…”
Section: Definition Of Antibiotics and Outpatient Visitsmentioning
confidence: 99%
“…Following previous studies, 17,18 second-to four-generation cephalosporins, fluoroquinolones, macrolides, combinations of penicillins, and streptomycins were classified as broad-spectrum antibacterial agents. Other antibiotics were classified as narrow-spectrum, such as beta-lactamase sensitive penicillins and first-generation cephalosporins.…”
Section: Definition Of Antibiotics and Outpatient Visitsmentioning
confidence: 99%
“…These diseases are mostly caused by viruses and empirical antimicrobials are not necessary for otherwise healthy patients (here, ‘otherwise healthy’ indicates that except for acute infectious diarrhea, the patients had no other medical conditions requiring treatment), particularly in developed countries [ 10 , 11 ]. A previous Japanese study analyzing data from 2012 to 2015 showed that 40.5% of antimicrobials were prescribed for viral upper respiratory infections, 25.8% for gastrointestinal infections, and 6.7% for nonbacterial gastrointestinal infections [ 12 ]. In response to the Global Action Plan, similar to other nations, the Government of Japan prepared the National Action Plan on AMR in 2016 [ 13 ] and the Ministry of Health, Labour, and Welfare (MHLW) of Japan drafted the Manual of Antimicrobial Stewardship in 2017, particularly regarding acute respiratory tract infection and acute infectious diarrhea [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have examined the role of antimicrobial stewardship in acute respiratory tract infections [ 6 , 15 , 16 ], few studies have examined this issue in relation to diarrhea in Japan, excluding a database study in children [ 17 ] and in all ages [ 12 ], but both of these studies were based on data up to 2015 and did not compare data between before and after the preparation of the National Action Plan and the manual. To implement measures for national antimicrobial stewardship for acute infectious diarrhea, understanding is required of the epidemiological characteristics of and antimicrobial prescriptions for acute infectious diarrhea.…”
Section: Introductionmentioning
confidence: 99%